Pengabdian Mengajar di Sekolah Dasar: Strategi Pembelajaran, Tantangan, dan Capaian Program di Desa Pandesari - Ananda Fredinand Perdana Putra; Safira Pramestia; Yolan Permana; Annisa Nurwahyu Islami (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2025)
Community-based teaching programs in primary schools need to be designed around students’ actual learning needs rather than merely providing additional classroom assistance. This community service program aimed to support students’ learning at SDN 1 and SDN 2 Pandesari, Pujon District, East Java, focusing on reading assistance for lower-grade students and student engagement in classroom learning. The program was implemented through the Student Community Service Program (Kuliah Kerja Mahasiswa or KKM) in four stages: needs identification, planning, implementation, and evaluation and reflection. Based on needs identified in collaboration with teachers, three main strategies were implemented: reading assistance for students in grades 1–3, game-based learning, and an interpersonal approach. The results indicated that game-based learning helped create a more interactive classroom environment and provided greater opportunities for student participation, while the interpersonal approach supported more open communication between university students and pupils. Students who participated more consistently in reading assistance also showed observable progress in their reading activities during the program. However, this progress cannot yet be interpreted as a measurable improvement in reading proficiency because standardized pre- and post-program assessments were not administered. The program indicates that alignment between instructional strategies and students’ needs, teacher involvement, and continuity of assistance are important elements of community-based teaching programs in primary schools.